2008
DOI: 10.1039/b802745e
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic synthesis of titania nanoparticles induced by protamine

Abstract: Protamine, a kind of cationic protein extracted from sperm nuclei, was employed for the first time in vitro to induce the formation of a titania/protamine nanoparticle composite from a water-stable titanium precursor, titanium(IV) bis(ammonium lactato) dihydroxide (Ti-BALDH). The resulting titania/protamine nanoparticle composite was extensively characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 38 publications
2
106
0
Order By: Relevance
“…The broad band at around 450-700 cm À1 could be attributed to the absorption of Ti-O-Ti, which indicated the formation of titania. [40] Furthermore, with the increase of layer number, the peaks discussed above displayed an increasing trend, further confirming the successive growth of multilayer in the LbL assembly. X-ray photoelectron spectroscopy (XPS) was conducted to investigate the surface element composition of (protamine/titania) 5 .…”
Section: Morphology and Structure Of Protamine-titania Hybrid Microcasupporting
confidence: 49%
See 4 more Smart Citations
“…The broad band at around 450-700 cm À1 could be attributed to the absorption of Ti-O-Ti, which indicated the formation of titania. [40] Furthermore, with the increase of layer number, the peaks discussed above displayed an increasing trend, further confirming the successive growth of multilayer in the LbL assembly. X-ray photoelectron spectroscopy (XPS) was conducted to investigate the surface element composition of (protamine/titania) 5 .…”
Section: Morphology and Structure Of Protamine-titania Hybrid Microcasupporting
confidence: 49%
“…This clearly revealed that the titanium elements were in the oxidation state IV, corresponding to Ti 4þ (TiO 2 ). [40] These results further suggested that these microcapsules assuredly comprised of protamine and titania.…”
Section: Morphology and Structure Of Protamine-titania Hybrid Microcamentioning
confidence: 61%
See 3 more Smart Citations